Molybdenum-modified nickel-manganese-iron-based ternary composite positive electrode material as well as preparation method and application thereof

Through the combined modification of molybdenum doping and Na2MoO4 coating, the problem of mechanical stress and interface side reactions caused by phase change during charging of the nickel-manganese-iron-based cathode material was solved, and the structural stability and electrochemical performance were improved.

CN119361674APending Publication Date: 2025-01-24TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411503129.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Nickel-ferromanganese base oxide positive electrode material is charged to high voltage due to O3-P3-O3' phase change, causing the anisotropic lattice of the crystal c-axis to shrink, resulting in mechanical stress, resulting in particle microcracking, crushing and electronic isolation. This in turn causes side reactions and harmful phase transitions at the electrode/electrolyte interface, affecting electrochemical performance and safety.

Method used

Through the combined modification of molybdenum doping and surface coating layer Na2MoO4, the molybdenum element is doped in the bulk phase to replace some iron sites, stabilizing the crystal structure and promoting particle refinement. The coating layer inhibits the interface side reactions between the electrode and the electrolyte. .

Benefits of technology

Effectively stabilize the crystal structure, reduce stress accumulation, improve structural stability and surface interface stability, significantly improve electrochemical properties and inhibit security problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361674A_ABST
    Figure CN119361674A_ABST
Patent Text Reader

Abstract

The invention discloses a molybdenum-modified nickel-manganese-iron-based ternary composite positive electrode material and a preparation method and application thereof, the positive electrode material comprises a molybdenum-doped nickel-manganese-iron-based oxide and a coating layer coating the surface of the nickel-manganese-iron-based oxide, and the molecular formula of the positive electrode material is NaNi < x > Mn < y > Fe < z > Mo O < 2 > (at) (Na2MoO < 4 >) b. The preparation method comprises the following steps: mixing a precursor containing nickel, manganese and iron, a modifier containing molybdenum and a sodium source to obtain a raw material mixture, adding an organic solvent, then carrying out wet ball milling to obtain raw material powder, and sintering the raw material powder in an air atmosphere at 800-880 DEG C; according to the positive electrode material provided by the invention, the molybdenum element is subjected to bulk phase doping to replace part of iron sites, so that a crystal structure can be effectively stabilized, primary grain refinement is promoted, stress accumulation is relieved, and the structural stability is improved; the coating layer Na2MoO4 can effectively inhibit the interface side reaction between the electrode and the electrolyte, relieve the surface and interface phase change and transition metal dissolution, and improve the surface and interface stability; when being used as a positive electrode material, the material has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and more specifically, to a molybdenum-modified nickel-manganese-iron-based ternary oxide composite positive electrode material and a preparation method and application thereof. Background Art

[0002] Fossil energy is the fundamental guarantee for human survival and the development of society, the country, and science and technology. However, the large amount of irreversible consumption has put humans in the face of energy crises and environmental disasters. Therefore, the development of clean energy such as high-efficiency, abundant resources, and environmentally friendly energy has become the current mainstream development direction. For example, it is an effective solution to convert clean energy such as solar energy, wind energy, hydropower, and tidal energy into electrical energy through electrochemical large-scale energy storage to achieve grid connection. Sodium-ion batteries are expected to be the primary electrochemical energy storage method in large-scale energy storage due to their advantages such as abundant resources and low cost.

[0003] In order to meet the requirements of high energy density, low cost and long cycle life of sodium-ion batteries in large-scale energy storage, nickel-manganese-iron-based hierarchical cathodes have been considered as one of the most preferred cathode materials for sodium-ion batteries due to their high discharge specific capacity (>130 mAh / g), relatively low cost and toxicity. However, when charged to high voltage, the O3-P3-O3' phase transition causes a sudden anisotropic lattice contraction of the crystal c-axis, resulting in the generation and accumulation of a large amount of mechanical stress inside the particles, further leading to the formation of microcracks, crushing and electronic isolation of active particles. The particle microcracks provide a fast channel for the electrolyte to penetrate into the particles, accelerate the parasitic side reactions at the internal electrode / electrolyte interface, and lead to the formation, aggregation and continuous impedance growth of harmful phase transitions such as rock salt phase. In addition, H in the electrolyte + These types of oxides can severely corrode the surface of active particles, leading to the dissolution of transition metal ions and the release of air, and further causing serious voltage decay and safety problems. The large-scale application of O3 nickel-manganese-iron-based structured oxide positive electrodes mainly depends on solving these bottleneck problems.

[0004] In order to solve the above problems, the existing technologies generally focus on modifying the positive electrode materials by ion doping, surface coating, grain morphology control, etc.

[0005] However, the single modification in the existing technology has certain defects: ion doping and grain morphology control have very limited modification effects on the surface interface, while surface coating has very weak control on the bulk crystal structure, which greatly limits the improvement of the comprehensive electrochemical performance and safety performance of the O3 phase positive electrode by single modification treatment. Therefore, people combine the first step of bulk doping and the second step of surface coating treatment to improve the electrochemical performance of the material, but at the same time it will bring a series of problems, including complicated processes, high costs, sample contamination, etc. Summary of the invention

[0006] Based on the defects existing in the prior art, the purpose of the present invention is to provide a molybdenum-modified nickel-manganese-iron based ternary composite positive electrode material and its preparation method and application.

[0007] According to one aspect of the present invention, a molybdenum-modified nickel-manganese-iron-based ternary layered composite positive electrode material is provided, characterized in that the positive electrode material comprises: a molybdenum-doped nickel-manganese-iron-based oxide and a coating layer coated on the surface of the nickel-manganese-iron-based oxide, and the molecular formula of the positive electrode material is: NaNi x Mn y Fe z Mo a O2@(Na2MoO4) b ;in: 0≤x≤0.5, 0≤y≤0.5, 0≤z≤0.5, 0.001≤a≤0.05, 0.001≤b≤0.05, and x+y+z+a=1.

[0008] In a preferred embodiment, 0.2≤x≤0.5, 0.2≤y≤0.5, and 0.2≤z≤0.5.

[0009] According to another aspect of the present invention, there is provided a method for preparing a molybdenum-modified nickel-manganese-iron-based ternary layered composite positive electrode material, comprising the following steps: Step 1: Mix a precursor containing nickel, manganese and iron, a modifier and a sodium source to obtain a raw material mixture, add an organic solvent, and then perform wet ball milling to obtain a raw material powder; the modifier is a molybdenum-containing compound; Step 2: Sintering is performed in an air atmosphere at 800-880° C. to obtain the molybdenum-modified nickel-manganese-iron based ternary layered composite positive electrode material.

[0010] In a preferred embodiment, in step 1, during wet ball milling, the mass ratio of material, balls and organic solvent is 1: (1.0-2.0): (0.8-1.2); the rotation speed is 300-800 rpm / min.

[0011] In a preferred embodiment, in step 1, the modifier is MoO3, MoC, Mo(NO3)3, C 10 H 14 At least one of MoO6 and Mo(OH)3.

[0012] In a preferred embodiment, in step 1, the sodium source is selected from at least one of sodium carbonate, sodium hydroxide, sodium acetate, sodium oxalate and sodium nitrate.

[0013] In a preferred embodiment, in step 2, the temperature is first raised to 400-600° C. and kept for 3-9 hours, and then sintered at 800-880° C. for 10-24 hours.

[0014] In a preferred embodiment, in step 2, after sintering is completed, the temperature is lowered to room temperature at a rate of 1.5-9.5° C. / min.

[0015] According to another aspect of the present invention, a positive electrode is provided, which includes the positive electrode material described above or the positive electrode material obtained by the preparation method described above.

[0016] According to another aspect of the present invention, a sodium ion battery is provided, comprising the positive electrode described above.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: In the positive electrode material provided by the present invention, molybdenum element is bulk-doped to replace part of the iron sites, which can effectively stabilize the crystal structure, promote the grain refinement of primary particles, relieve the accumulation of stress, and improve the structural stability; and the coating layer Na2MoO4 can effectively inhibit the interface side reaction between the electrode and the electrolyte, relieve the surface interface phase change and transition metal dissolution, and improve the surface interface stability; as a positive electrode material, it has excellent electrochemical properties.

[0018] The preparation method of the composite electrode material provided by the present invention adopts wet ball milling and direct calcination after mixing, and realizes bulk doping, in-situ surface coating and primary grain refinement synergistic modification of the nickel-manganese-iron based ternary oxide in a one-step method, which not only improves the structural stability of the high-nickel positive electrode material, but also reduces the process steps, reduces the use of chemical solvents, shortens the synthesis time, and reduces the process cost.

[0019] The preparation method of the present invention has simple process and is suitable for promotion. It is a method for effectively improving the structural stability of O3 phase layered positive electrode materials and inhibiting microcracks and surface interface degradation during the cycle process. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM photograph of the NMF sample prepared in Comparative Example 1 of the present invention at a magnification of 2400 times; Figure 2 This is a SEM photograph of the NMF-Mo1 sample prepared in Example 1 of the present invention at a magnification of 2400 times; Figure 3 X-ray diffraction patterns of the NMF sample prepared in Comparative Example 1 of the present invention and the NMF-Mo1 sample prepared in Example 1; Figure 4 The NMF sample prepared in Comparative Example 1 of the present invention and the NMF-Mo1 sample prepared in Example 1 are used as positive electrode materials for sodium ion batteries to prepare positive electrode sheets. The first specific capacity-voltage curve at a current density of 0.1 C for button cells.

[0021] Figure 5 The NMF sample prepared in comparative example 1 of the present invention and the NMF-Mo1 sample prepared in example 1 are used as positive electrode materials for lithium-ion batteries to prepare positive electrode sheets. The mass specific capacity curve of button cells cycled 50 times at a current density of 1 C. DETAILED DESCRIPTION

[0022] A typical embodiment of the present invention provides a molybdenum-modified nickel-manganese-iron-based ternary layered composite positive electrode material, which comprises: a molybdenum-doped nickel-manganese-iron-based oxide and a coating layer coated on the surface of the nickel-manganese-iron-based oxide. The molecular formula of the positive electrode material is: NaNi x Mn y Fe z Mo a O2@(Na2MoO4) b ;in: 0≤x≤0.5, 0≤y≤0.5, 0≤z≤0.5, 0.001≤a≤0.05, 0.001≤b≤0.05, and x+y+z+a=1. Preferably, in the above molecular formula, 0.2≤x≤0.5, 0.2≤y≤0.5, 0.2≤z≤0.5.

[0023] In this embodiment, the molybdenum element is uniformly dispersed in the nickel-manganese-iron-based ternary oxide, and the coating layer is uniformly coated on the surface of the nickel-manganese-iron-based ternary oxide. The bulk doping of the molybdenum element to replace part of the transition metal sites can effectively stabilize the crystal structure, inhibit the P3-O'3 phase transformation, promote the refinement of the primary particles, relieve the accumulation of stress, and improve the structural stability; while the surface coating layer Na2MoO4 can effectively inhibit the interface side reaction between the electrode and the electrolyte, relieve the surface interface phase change and transition metal dissolution, and improve the surface interface stability.

[0024] Another typical embodiment of the present invention provides a method for preparing a molybdenum-modified nickel-manganese-iron based ternary layered composite positive electrode material, which comprises the following steps: Step 1: Mix a precursor containing nickel, manganese and iron, a modifier and a sodium source to obtain a raw material mixture, add an organic solvent, and then perform wet ball milling to obtain a raw material powder; the modifier is a molybdenum-containing compound.

[0025] In this embodiment, the role of the modifier organic solvent is to prevent the raw materials from agglomerating and settling; the modifier is selected from MoO3, MoC, Mo(NO3)3, C 10 H 14 At least one of MoO6 and Mo(OH)3.

[0026] In this embodiment, the precursor containing nickel, manganese and iron includes at least one compound containing at least one of nickel, manganese and iron, including but not limited to compounds containing only nickel, compounds containing only manganese, compounds containing only iron; or compounds containing any two or three of nickel, manganese and iron; the compounds include but are not limited to oxides, nitrates, hydroxides, chlorides, acetates, carbonates, etc.

[0027] In this embodiment, the sodium source is a sodium compound, including but not limited to at least one of sodium carbonate, sodium hydroxide, sodium acetate, sodium oxalate and sodium nitrate.

[0028] In this embodiment, the organic solvent is ethanol and / or isopropanol.

[0029] Precursors and modifiers containing nickel, manganese and iron are mixed according to a stoichiometric ratio, and the molar excess coefficient of the sodium source added is 1-10% to prevent evaporation loss during high-temperature sintering.

[0030] Preferably, in step 1, during wet ball milling, the mass ratio of material, ball and organic solvent is 1: (1.0-2.0): (0.8-1.2), the ball milling speed is 300-800 rpm / min, and the ball milling time is 1-36h.

[0031] After ball milling, the method further includes drying the mixture, specifically, vacuum drying the mixture at a temperature of 80-120° C. for 8-14 hours to obtain a raw material powder.

[0032] Step 2: Sintering is performed in an air atmosphere at 800-880° C. to obtain the molybdenum-modified nickel-manganese-iron based ternary layered composite positive electrode material.

[0033] In a preferred embodiment, the temperature is first raised to 400-600°C and kept for 3-9 hours, and then kept at 800-880°C for 10-24 hours. Further, the temperature is raised to 400-600°C at a rate of 0.5-5°C / min and kept for 5-8 hours, and then raised to 800-880°C at a rate of 0.5-5°C / min and kept for 10-24 hours.

[0034] In step 2, after sintering, the temperature is lowered to room temperature at a rate of 1.5-9.5°C / min. In a preferred embodiment, the temperature lowering rate is 1.5-5.5°C / min.

[0035] The technical scheme claimed in the present invention is further described below by some examples. However, the examples and comparative examples are used to explain the embodiments of the present invention and do not exceed the scope of the subject matter of the present invention. The protection scope of the present invention is not limited by the examples. Unless otherwise specified, the materials and reagents used in the present invention can be obtained from commercial products in the art. Example 1

[0036] The embodiment of the present invention provides a method for preparing a molybdenum-doped, surface-coated, and grain-refined synergistically modified O3-phase composite positive electrode material, which specifically includes the following steps: S1, weigh 0.01 mol of precursor Ni 0.333 Mn 0.334 Fe 0.333 (OH)2, 0.0001 mol modifier C 10 H 14 MoO6 and 0.005279 mol of sodium source Na2CO3 are placed in an agate ball mill to obtain a raw material mixture, wherein Na2CO3 is in excess of 5% mol to prevent evaporation loss during high-temperature sintering; then solvent ethanol is added, wherein the mass ratio of ethanol to the raw material mixture is 1:1; S2, placing the ball mill jar loaded with the raw material mixture in S1 in a ball mill, ball milling at a speed of 400 rpm / min for 12 h, and then vacuum drying at 80°C for 12 h to obtain a uniformly mixed raw material powder; S3, transfer the raw material powder in S2 to a corundum ark, and then place it in an air atmosphere, first heat it to 550 ° C at a rate of 2 ° C / min and keep it warm for 5 h, then heat it to 850 ° C at a rate of 5 ° C / min and keep it warm for 15 h, and then cool it to room temperature at a rate of 3 ° C / min to obtain a nickel-manganese-iron based ternary composite positive electrode material NMF-Mo1 with molybdenum doping, coating, and grain refinement synergistic modification, and the molecular formula is: NaNi 0.333 Mn 0.334 Fe 0.3258 Mo 0.0072 O2@(Na2MoO4) 0.0028 , and its SEM and XRD patterns are shown as follows: Figure 2 and Figure 3 shown. Example 2

[0037] The embodiment of the present invention provides a method for preparing a molybdenum-doped, coated, and grain-refined synergistically modified O3-phase composite positive electrode material, which specifically includes the following steps: S1, weigh 0.01 mol of precursor Ni 0.333 Mn 0.334 Fe 0.333 (OH)2, 0.00005 mol Modifier C 10 H 14 MoO6 and 0.005264 mol of sodium source Na2CO3 are placed in an agate ball mill to obtain a raw material mixture, wherein Na2CO3 is in excess of 5% mol to prevent evaporation loss during high-temperature sintering; then solvent ethanol is added, wherein the mass ratio of ethanol to the raw material mixture is 1:1; S2, placing the ball mill jar loaded with the raw material mixture in S1 in a ball mill, ball milling at a speed of 400 rpm / min for 12 h, and then vacuum drying at 80°C for 12 h to obtain a uniformly mixed raw material powder; S3, transfer the raw material powder in S2 to a corundum ark, and then place it in an air atmosphere, first heat it to 550 ° C at a rate of 2 ° C / min and keep it warm for 5 h, then heat it to 850 ° C at a rate of 3 ° C / min and keep it warm for 15 h, and then cool it to room temperature at a rate of 3 ° C / min to obtain a nickel-manganese-iron based ternary composite positive electrode material NMF-Mo0.5 with molybdenum doping, coating, and grain refinement synergistic modification, and the molecular formula is: NaNi 0.333 Mn 0.334 Fe 0.3294 Mo 0.0036 O2@(Na2MoO4) 0.0014 . Example 3

[0038] The embodiment of the present invention provides a method for preparing a molybdenum-doped, surface-coated, and grain-refined synergistically modified O3-phase composite positive electrode material, which specifically includes the following steps: S1, weigh 0.01 mol of precursor Ni 0.333 Mn 0.334 Fe 0.333 (OH)2, 0.0002 mol Modifier C 10 H 14 MoO6 and 0.00530 mol of sodium source Na2CO3 are placed in an agate ball mill to obtain a raw material mixture, wherein Na2CO3 is in excess of 5% mol to prevent evaporation loss during high-temperature sintering; then solvent ethanol is added, wherein the mass ratio of ethanol to the raw material mixture is 1:1; S2, placing the ball mill jar loaded with the raw material mixture in S1 in a ball mill, ball milling at a speed of 400 rpm / min for 12 h, and then vacuum drying at 80°C for 12 h to obtain a uniformly mixed raw material powder; S3, transfer the raw material powder in S2 to a corundum ark, and then place it in an air atmosphere, first heat it to 550 ° C at a rate of 2 ° C / min and keep it warm for 5 h, then heat it to 850 ° C at a rate of 5 ° C / min and keep it warm for 15 h, and then cool it to room temperature at a rate of 3 ° C / min to obtain a nickel-manganese-iron based ternary composite positive electrode material NMF-Mo2 with molybdenum doping, coating, and grain refinement synergistic modification, and the molecular formula is: NaNi 0.333 Mn 0.334 Fe 0.3186 Mo 0.0144 O2@(Na2MoO4) 0.0056 . Example 4

[0039] The embodiment of the present invention provides a method for preparing a molybdenum-doped, surface-coated, and grain-refined synergistically modified O3-phase composite positive electrode material, which specifically includes the following steps: S1, weigh 0.01 mol of precursor Ni 0.333 Mn 0.334 Fe 0.333 (OH)2, 0.0003 mol Modifier C 10 H 14 MoO6 and 0.005338 mol of sodium source Na2CO3 are placed in an agate ball mill to obtain a raw material mixture, wherein Na2CO3 is in excess of 5% mol to prevent evaporation loss during high-temperature sintering; then solvent ethanol is added, wherein the mass ratio of ethanol to the raw material mixture is 1:1; S2, placing the ball mill jar loaded with the raw material mixture in S1 in a ball mill, ball milling at a speed of 400 rpm / min for 12 h, and then vacuum drying at 80°C for 12 h to obtain a uniformly mixed raw material powder; S3, transfer the raw material powder in S2 to a corundum ark, and then place it in an air atmosphere, first heat it to 550 ° C at a rate of 2 ° C / min and keep it warm for 5 h, then heat it to 850 ° C at a rate of 5 ° C / min and keep it warm for 15 h, and then cool it to room temperature at a rate of 3 ° C / min to obtain a nickel-manganese-iron based ternary composite positive electrode material NMF-Mo3 with molybdenum doping, coating, and grain refinement synergistic modification, and the molecular formula is: NaNi 0.332 Mn 0.335 Fe 0.3114 Mo 0.0216 O2@(Na2MoO4) 0.0084 . Example 5

[0040] The embodiment of the present invention provides a method for preparing a molybdenum-doped, surface-coated, and grain-refined synergistically modified O3-phase composite positive electrode material, which specifically includes the following steps: S1, weigh 0.01 mol of precursor Ni 0.333 Mn 0.334 Fe 0.333 (OH)2, 0.0001 mol modifier C 10 H 14 MoO6 and 0.005279 mol of sodium source Na2CO3 are placed in an agate ball mill to obtain a raw material mixture, wherein Na2CO3 is in excess of 5% mol to prevent evaporation loss during high-temperature sintering; then solvent ethanol is added, wherein the mass ratio of ethanol to the raw material mixture is 1:1; S2, placing the ball mill jar loaded with the raw material mixture in S1 in a ball mill, ball milling at a speed of 400 rpm / min for 12 h, and then vacuum drying at 80°C for 12 h to obtain a uniformly mixed raw material powder; S3. Transfer the raw material powder in S2 into a corundum ark, and then place it in an air atmosphere, first heat it to 550 °C at a rate of 2 °C / min and keep it warm for 5 h, then heat it to 800 °C at a rate of 5 °C / min and keep it warm for 15 h, and then cool it to room temperature at a rate of 3 °C / min to obtain the molybdenum-doped, coated, and grain-refined synergistically modified nickel-manganese-iron based ternary composite positive electrode material NMF-Mo1-800 °C. Example 6

[0041] The embodiment of the present invention provides a method for preparing a molybdenum-doped, surface-coated, and grain-refined synergistically modified O3-phase composite positive electrode material, which specifically includes the following steps: S1, weigh 0.01 mol of precursor Ni 0.333 Mn 0.334 Fe 0.333 (OH)2, 0.0001 mol modifier C 10 H 14 MoO6 and 0.005279 mol of sodium source Na2CO3 are placed in an agate ball mill to obtain a raw material mixture, wherein Na2CO3 is in excess of 5% mol to prevent evaporation loss during high-temperature sintering; then solvent ethanol is added, wherein the mass ratio of ethanol to the raw material mixture is 1:1; S2, placing the ball mill jar loaded with the raw material mixture in S1 in a ball mill, ball milling at a speed of 400 rpm / min for 12 h, and then vacuum drying at 80°C for 12 h to obtain a uniformly mixed raw material powder; S3. Transfer the raw material powder in S2 into a corundum ark, and then place it in an air atmosphere, first heat it to 550 ℃ at a rate of 2 ℃ / min and keep it warm for 5 h, then heat it to 820 ℃ at a rate of 5 ℃ / min and keep it warm for 15 h, and then cool it to room temperature at a rate of 3 ℃ / min to obtain the molybdenum-doped, coated, grain-refined synergistically modified nickel-manganese-iron based ternary composite positive electrode material NMF-Mo1-820℃. Example 7

[0042] The embodiment of the present invention provides a method for preparing a molybdenum-doped, surface-coated, and grain-refined synergistically modified O3-phase composite positive electrode material, which specifically includes the following steps: S1, weigh 0.01 mol of precursor Ni 0.333 Mn 0.334 Fe 0.333 (OH)2, 0.0001 mol modifier C10 H 14 MoO6 and 0.005279 mol of sodium source Na2CO3 are placed in an agate ball mill to obtain a raw material mixture, wherein Na2CO3 is in excess of 5% mol to prevent evaporation loss during high-temperature sintering; then solvent ethanol is added, wherein the mass ratio of ethanol to the raw material mixture is 1:1; S2, placing the ball mill jar loaded with the raw material mixture in S1 in a ball mill, ball milling at a speed of 400 rpm / min for 12 h, and then vacuum drying at 80°C for 12 h to obtain a uniformly mixed raw material powder; S3, the raw material powder in S2 is transferred to a corundum ark, and then placed in an air atmosphere, first heated to 550 ° C at a rate of 2 ° C / min and kept warm for 5 h, then heated to 880 ° C at a rate of 5 ° C / min and kept warm for 15 h, and then cooled to room temperature at a rate of 3 ° C / min to obtain a nickel-manganese-iron based ternary composite positive electrode material NMF-Mo1-880 ° C with molybdenum doping, coating, and grain refinement synergistic modification. Comparative Example 1 This comparative example provides a method for preparing an O3 phase positive electrode material, comprising the following steps: S1, weigh 0.01 mol of precursor Ni 0.333 Mn 0.334 Fe 0.333 (OH)2 and 0.00525 mol of sodium source Na2CO3 are placed in an agate ball mill to obtain a raw material mixture, wherein Na2CO3 is in excess of 5% mol to prevent evaporation loss during high-temperature sintering; then solvent ethanol is added, wherein the mass ratio of the raw material mixture to ethanol is 1:1; S2, placing the ball mill jar loaded with the raw material mixture in S1 in a ball mill, ball milling at a speed of 400 rpm / min for 12 h, and then vacuum drying at 80°C for 12 h to obtain a uniformly mixed raw material powder; S3, the raw material powder in S2 was transferred to a corundum ark, and then placed in an air atmosphere, first heated to 500 °C at a rate of 2 °C / min and kept warm for 5 h, then heated to 850 °C at a rate of 5 °C / min and kept warm for 15 h, and then cooled to room temperature at a rate of 3 °C / min to obtain a nickel-manganese-iron based ternary positive electrode material NMF, whose SEM and XRD patterns are shown as follows: Figure 1 and Figure 3 shown.

[0043] Comparative Example 2 This comparative example provides a method for preparing an O3 phase positive electrode material, comprising the following steps: S1, weigh 0.01 mol of precursor Ni 0.333 Mn 0.334Fe 0.333 (OH)2, 0.0001 mol modifier C 10 H 14 MoO6 and 0.005279 mol of sodium source Na2CO3 are placed in an agate ball mill to obtain a raw material mixture, wherein Na2CO3 is in excess of 5% mol to prevent evaporation loss during high-temperature sintering; then solvent ethanol is added, wherein the mass ratio of the raw material mixture to ethanol is 1:1; S2, placing the ball mill jar loaded with the raw material mixture in S1 in a ball mill, ball milling at a speed of 400 rpm / min for 12 h, and then vacuum drying at 80°C for 12 h to obtain a uniformly mixed raw material powder; S3. Transfer the raw material powder in S2 into a corundum ark, and then place it in an argon atmosphere, first heat it to 500 °C at a rate of 2 °C / min and keep it warm for 5 h, then heat it to 850 °C at a rate of 5 °C / min and keep it warm for 15 h, and then cool it to room temperature at a rate of 3 °C / min to obtain the nickel-manganese-iron based ternary positive electrode material NMF-Mo1-Ar.

[0044] Comparative Example 3 This comparative example provides a method for preparing a molybdenum-doped, surface-coated, grain-refined synergistically modified O3 phase composite positive electrode material, which specifically comprises the following steps: S1, weigh 0.01 mol of precursor Ni 0.333 Mn 0.334 Fe 0.333 (OH)2, 0.0001 mol modifier C 10 H 14 MoO6 and 0.005279 mol of sodium source Na2CO3 are placed in an agate ball mill to obtain a raw material mixture, wherein Na2CO3 is in excess of 5% mol to prevent evaporation loss during high-temperature sintering; then solvent ethanol is added, wherein the mass ratio of ethanol to the raw material mixture is 1:1; S2, placing the ball mill jar loaded with the raw material mixture in S1 in a ball mill, ball milling at a speed of 400 rpm / min for 12 h, and then vacuum drying at 80°C for 12 h to obtain a uniformly mixed raw material powder; S3. Transfer the raw material powder in S2 into a corundum ark, and then place it in an air atmosphere, first heat it to 550 ℃ at a rate of 2 ℃ / min and keep it warm for 5 h, then heat it to 700 ℃ at a rate of 5 ℃ / min and keep it warm for 15 h, and then cool it to room temperature at a rate of 3 ℃ / min to obtain the molybdenum-doped, coated, and grain-refined synergistically modified nickel-manganese-iron based ternary composite positive electrode material NMF-Mo1-700℃.

[0045] The NMF sample prepared in Comparative Example 1 and the NMF-Mo1 sample prepared in Example 1 were characterized; wherein, Figure 1 This is a SEM photograph of the NMF sample prepared in Example 1 of the present invention at a magnification of 2400 times; Figure 2 This is a SEM photograph of the NMF-Mo1 sample prepared in Example 2 of the present invention at a magnification of 2400 times.

[0046] The NMF sample prepared in Comparative Example 1 and the NMF-Mo1 sample prepared in Example 1 were characterized; wherein, Figure 1 This is a SEM photograph of the NMF sample prepared in Comparative Example 1 of the present invention at a magnification of 2400 times; Figure 2 This is a SEM photograph of the NMF-Mo1 sample prepared in Example 1 of the present invention at a magnification of 2400 times.

[0047] from Figure 1 It can be seen that the prepared NMF sample is composed of secondary microspheres accumulated by flake-like primary nanoparticles, and the average size is about 9 μm; in addition, compared Figure 1 and Figure 2 It can be found that compared with the NMF sample prepared in Comparative Example 1, the primary particle morphology of the modified NMF-Mo1 nickel-manganese-iron-based ternary composite positive electrode sample prepared in Example 1 has changed significantly, from large flake-like rough grains to small smooth grains, indicating that the addition of a modifier can refine the primary grains.

[0048] Figure 3 X-ray diffraction patterns of the NMF sample prepared in Comparative Example 1 of the present invention and the NMF-Mo1 sample prepared in Example 1.

[0049] from Figure 3 It can be seen that the main diffraction peaks of the prepared samples are all layered structures, and the corresponding space group is R-3 m; it is worth noting that some new characteristic peaks appear after Mo modification, corresponding to the Na2MoO4 phase, proving that a Na2MoO4 coating layer is generated.

[0050] The samples prepared in Examples 1-7 and Comparative Examples 1-3 were respectively used as positive electrode materials for sodium ion batteries to prepare positive electrode sheets. The specific process is as follows: (1) The prepared powdered cathode material was mixed with Super P (conductive agent) and polyvinylidene fluoride (PVDF, binder) in a mass ratio of 8:1:1, and an appropriate amount of 1-methylpyrrolidone (NMP) was added as a dispersant, and the mixture was ground into a slurry. Subsequently, the slurry was evenly coated on an aluminum foil, vacuum dried at 120 °C for 12 h, and transferred to an argon atmosphere glove box for standby use. (2) A half-cell was assembled in an argon atmosphere glove box, using a sodium metal sheet as the counter electrode and NaClO4 / ethylene carbonate (PC:EC = 1:1 + 5% FEC by volume) as the electrolyte. A button cell of the assembled specification was CR-2016, and the charge and discharge test was performed using the constant current charge and discharge mode.

[0051] Figure 4 The first charge and discharge curves of button cells of which the NMF sample prepared in Comparative Example 1 of the present invention and the NMF-Mo1 sample prepared in Example 1 are used as positive electrode materials for sodium ion batteries to prepare positive electrode sheets; Figure 4 It can be seen that the first cycle discharge capacity is 154.2 mAh / g (NMF) and 156.3 (NMF-Mo1) mAh / g, and the corresponding coulombic efficiency is 84.9% (NMF) and 88.3% (NMF-Mo1).

[0052] Table 1 below shows the results of the first discharge capacity and coulombic efficiency of button cells of positive electrode sheets prepared by using the samples prepared in the embodiments and comparative examples of the present invention as positive electrode materials for sodium ion batteries.

[0053] Table 1 The first discharge capacity and coulombic efficiency of each sample after preparing the positive electrode sheet

[0054] Combination Figure 4 From the results in Table 1, it can be seen that the first coulombic efficiency of button cells for preparing positive electrode sheets of sodium ion battery positive electrode materials prepared by the samples after synergistic modification of doping, coating and grain refinement is significantly improved, indicating that the irreversible capacity loss of the nickel-manganese-iron based ternary composite positive electrode material after synergistic modification of molybdenum doping, coating and grain refinement during the charge and discharge process has been significantly suppressed.

[0055] Figure 5 The mass specific capacity curve of the button cell in which the NMF sample prepared in Comparative Example 1 of the present invention and the NMF-Mo1 sample prepared in Example 1 are used as the positive electrode material for sodium ion batteries to prepare positive electrode sheets and cycled 50 times at a current density of 1 C; Figure 5 It can be seen that the retention rates after 50 cycles at 1 C current density are 91.0% (NMF-Mo1) and 83.5% (NMF).

[0056] Table 2 below shows the retention rates of button cells of positive electrode sheets prepared by samples prepared in various embodiments and comparative examples of the present invention after 50 cycles when used as positive electrode materials for sodium ion batteries.

[0057] Table 2 Retention rate of each sample after 50 cycles of preparing positive electrode sheets

[0058] Combination Figure 5 It can be seen from the results in Table 2 that the composite positive electrode material modified by molybdenum doping, coating and grain refinement can be used as a positive electrode material for sodium ion batteries to effectively inhibit the capacity decay of button batteries during the cycle process.

[0059] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A molybdenum-modified nickel-manganese-iron-based ternary layered composite positive electrode material, characterized in that: The positive electrode material comprises: a molybdenum-doped nickel-manganese-iron-based oxide and a coating layer coated on the surface of the nickel-manganese-iron-based oxide. The molecular formula of the positive electrode material is: NaNi x Mn y Fe z Mo a O2@(Na2MoO4) b ;in: 0≤x≤0.5, 0≤y≤0.5, 0≤z≤0.5, 0.001≤a≤0.05, 0.001≤b≤0.05, and x+y+z+a=1.

2. The molybdenum-modified nickel-manganese-iron-based ternary layered composite positive electrode material according to claim 1, characterized in that: 0.2≤x≤0.5, 0.2≤y≤0.5, 0.2≤z≤0.

5.

3. The method for preparing the molybdenum-modified nickel-manganese-iron-based ternary layered composite positive electrode material according to claim 1 or 2, characterized in that: The following steps are involved: Step 1: Mix a precursor containing nickel, manganese and iron, a modifier and a sodium source to obtain a raw material mixture, add an organic solvent, and then perform wet ball milling to obtain a raw material powder; the modifier is a molybdenum-containing compound; Step 2: Sintering is performed in an air atmosphere at 800-880° C. to obtain the molybdenum-modified nickel-manganese-iron based ternary layered composite positive electrode material.

4. The method for preparing the molybdenum-modified nickel-manganese-iron-based ternary layered composite positive electrode material according to claim 3, characterized in that: In step 1, during wet ball milling, the mass ratio of material, ball and organic solvent is 1: (1.0~2.0): (0.8~1.2); the rotation speed is 300~800 rpm / min.

5. The method for preparing the molybdenum-modified nickel-manganese-iron-based ternary layered composite positive electrode material according to claim 4, characterized in that: In step 1, the modifier is MoO3, MoC, Mo(NO3)3, C 10 H 14 At least one of MoO6 and Mo(OH)3.

6. The method for preparing the molybdenum-modified nickel-manganese-iron-based ternary layered composite positive electrode material according to claim 4 or 5, characterized in that: In step 1, the sodium source is selected from at least one of sodium carbonate, sodium hydroxide, sodium acetate, sodium oxalate and sodium nitrate.

7. The method for preparing the molybdenum-modified nickel-manganese-iron-based ternary layered composite positive electrode material according to claim 6, characterized in that: In step 2, the temperature is first raised to 400-600°C and kept at this temperature for 3-9 hours, and then sintered at 800-880°C for 10-24 hours.

8. The method for preparing the molybdenum-modified high-nickel ternary layered composite positive electrode material according to claim 7, characterized in that: In step 2, after sintering, the temperature is lowered to room temperature at a rate of 1.5-9.5°C / min.

9. A positive electrode, characterized in that The invention comprises the positive electrode material according to any one of claims 1 to 2 or the positive electrode material obtained by the preparation method according to any one of claims 3 to 8.

10. A sodium ion battery, characterized in that: Comprising the positive electrode as claimed in claim 9.

Citation Information

Cited By

  • High-energy-density sodium-ion battery sodium-rich positive electrode material and preparation method and application thereof

    CN120319789A